“You Are the Type of Person That Children Should Look up to as a Hero”: Parasocial Interaction on 38pitches.com - Sanderson, Jimmy (International Journal of Sport Communication, 2008)
This research explored people’s expression of parasocial interaction (PSI) on Boston Red Sox pitcher Curt Schilling’s blog, 38pitches.com. A thematic analysis using grounded theory (Glaser & Strauss, 1967) and constant comparative methodology of 1,337 postings on Schilling’s blog was conducted. Three parasocial aspects emerged from data analysis: identification, admonishment and advice giving, and criticism. The findings of the study provide support for previous research that suggests identification is a PSI component, and given the large presence of admonishment and criticism, the findings extend PSI theory by suggesting that PSI theory must account for and encompass negative relational behaviors. The results also indicate that people’s use of information and communication technologies is reconfiguring parasocial relationships as fans take an active role in soliciting and communicating with professional athletes, subsequently creating more opportunities for PSI to occur.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTEyMy9panNjLjEuMy4zMzc